PREGNANT HEIFER WITH CONGENITAL IMPERFORATE HYMEN - S. Satheshkumar; V. Prabaharan; S. Prakash; B. Puvarajan; M. Marutha Muthu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A rare incidence of persistent hymen in a pregnant crossbred heifer is reported. Gynaeco-clinical and ultrasonographic examination of crossbred heifer brought with a history of straining and vaginal prolapse revealed presence of imperforate hymen with accumulated mucopurulent secretion. Circumferential resection of the hymen was performed by applying Foley’s catheter retraction. Seven days post-surgery, animal was diagnosed to be pregnant for about 30 days. Based on the circumstantial observations the case might be considered as imperforate hymen with hydrocolpos.